Using EV Battery Packs for Vehicle-to-Grid Applications: An Economic Analysis - Lav, Agarwal (2016)
Electrification of the transportation segment has long been seen as a promising solution to reduce oil dependency and its environmental impacts. Electric Vehicles (EVs) can also be used as distributed energy resources providing ancillary services to the grid through Vehicle-to-grid (V2G). Incentives through V2G can lead to reduced EV ownership cost, thus increasing their acceptance and overall penetration. However, with high current battery prices and increased battery wear due to more frequent charging and discharging during V2G operations, it becomes economically challenging in realizing a profitable business model. This paper presents an economic analysis of various V2G offerings in consideration of market prices and battery wear cost. Aggregate Power Capacity, from a fleet of EVs is realized by modeling their driving pattern using trip chaining based on data from survey conducted, employment pattern and vehicular statistics. Battery life cycle is analyzed, for achievable cycle counts and net energy transferrable, operating to various depths of discharge (DoD) values. Economic analysis is performed using Singapore data.